2006
DOI: 10.1086/507539
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infections: In Harm’s Way: Infections in Deployed American Military Forces

Abstract: Hundreds of thousands of American service members have been deployed to Afghanistan and Iraq since 2001. With emphasis on the common infections and the chronic infections that may present or persist on their return to the United States, we review the data on deployment-associated infections. These infections include gastroenteritis; respiratory infection; war wound infection with antibiotic-resistant, gram-negative bacteria; Q fever; brucellosis; and parasitic infections, such as malaria and leishmaniasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 35 publications
3
125
0
2
Order By: Relevance
“…Supporting this hypothesis are several studies that have found an association between time spent off base and diarrhea: among U.S. personnel during Operations Iraqi Freedom and Enduring Freedom and during support operations in Egypt, diarrhea was more likely to be reported as the spent off base increased, which suggests increased consumption of locally prepared foods and drinks. 8,[23][24][25] These observations may also explain why the rate of diarrhea was so high among French forces in Chad, where during the period of this study, soldiers were exclusively deployed shortterm. An unpublished study (Pommier de Santi V, unpublished data) conducted in Chad during October 2007-February 2008 demonstrated that the incidence of diarrhea among French forces decreased during a period of combat between Chadian forces and rebels, when off-base travel was limited, mandating the consumption of pre-packaged meals ready to eat.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis are several studies that have found an association between time spent off base and diarrhea: among U.S. personnel during Operations Iraqi Freedom and Enduring Freedom and during support operations in Egypt, diarrhea was more likely to be reported as the spent off base increased, which suggests increased consumption of locally prepared foods and drinks. 8,[23][24][25] These observations may also explain why the rate of diarrhea was so high among French forces in Chad, where during the period of this study, soldiers were exclusively deployed shortterm. An unpublished study (Pommier de Santi V, unpublished data) conducted in Chad during October 2007-February 2008 demonstrated that the incidence of diarrhea among French forces decreased during a period of combat between Chadian forces and rebels, when off-base travel was limited, mandating the consumption of pre-packaged meals ready to eat.…”
Section: Discussionmentioning
confidence: 99%
“…The possible causes of the facial ulcer included cutaneous leishmaniasis, mycobacterial infection and fungal infection (e.g. sporotrichosis) 1 . Kabul, with two million citizens, has a yearly incidence of approximately 67,500 new cases of cutaneous leishmaniasis.…”
Section: Figurementioning
confidence: 99%
“…More recently, conflicts in Iraq and Afghanistan have led to significant advances in health care practices, in particular damage control surgery, damage control resuscitation, massive transfusion protocols, infection control and trauma reporting systems (Aronson et al, 2006;Eastridge et al, 2006;Hodgetts et al, 2007;Wildridge et al, 2012). A citation analysis of combat casualty research identified advances in the management of massive haemorrhage as the most significant contribution to military health care and that lessons learned have been adopted into civilian trauma paradigms (Orman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%